Inclusive Elements at Accessibility in Open Space and At-Taqwa Mosque Universitas Muhammadiyah Semarang - Safira, Lutfiana Devi; Kinasih, Kania (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2024)
The park at Universitas Muhammadiyah Semarang still does not fully meet the needs of blind people, because it still lacks guiding blocks, as well as the lack of other supporting elements that can hinder their ability to move. Thus, it is necessary to recommend a design solution that can improve access for blind people, especially on the path to the At-Taqwa Mosque. Against this background, this research seeks to design a guiding path for the visually impaired and signage that suits their needs in the green open space leading to the At-Taqwa Mosque. The design will consider the use of guiding blocks and braille signage as direction and information guides. An inclusive design plan is implemented so that all users, including people with other disabilities and the general public, can benefit optimally. The solutions proposed in this research, such as the addition of guiding blocks for navigation and a Braille signage as inclusive information, are designated based on universal design principles in Unimus’ green open space. The implementation of this solution not only supports the needs of the visually impaired but also creates an inclusive, comfortable, and accesible green open space for all campus users.